Digital Marketing, Hedonism, and Product Knowledge on the Interest in Using Paylater at A Hotel in Pontianak City - Muchammad Ariffin; Aisyah; Windi Pratiwi; Sabirin (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2026)
Advances in digital technology have driven significant changes in consumer behavior, including the adoption of financial services such as paylater, which is growing in the hospitality industry. This study aims to analyze the influence of digital marketing, hedonism, and product knowledge on the interest in using paylater at star-rated hotels in Pontianak City. The study employs a quantitative approach through a questionnaire survey using accidental sampling techniques on 88 respondents who are familiar with paylater services and have stayed at star-rated hotels. Data analysis was performed using smart-PLS 3.0. The results show that, partially, only product knowledge has a significant effect on the interest in using paylater (p-value = 0.000) with a dominant contribution of 64.5%. Meanwhile, digital marketing and hedonism did not have a significant individual effect. However, simultaneously, the three variables were able to explain 82.7% of the variability in interest in using paylater (R² = 0.827). These findings indicate that rational considerations based on product knowledge are more decisive than digital promotion factors and emotional motivation. The novelty of this research lies in testing an integrative model of the three variables in the context of star-rated hotels, which has previously been studied more extensively in the e-commerce sector. This study contributes to the development of consumer behavior literature and provides managerial implications regarding the importance of educational strategies in digital marketing for PayLater services. Abstrak - Kemajuan teknologi digital telah mendorong perubahan signifikan dalam perilaku konsumen, termasuk dalam adopsi layanan keuangan seperti paylater yang semakin berkembang di industri perhotelan. Penelitian ini bertujuan menganalisis pengaruh digital marketing, hedonisme, dan product knowledge terhadap minat penggunaan paylater pada hotel berbintang di Kota Pontianak. Penelitian menggunakan pendekatan kuantitatif melalui survei kuesioner dengan teknik accidental sampling terhadap 88 responden yang mengetahui layanan paylater dan pernah menginap di hotel berbintang. Analisis data dilakukan menggunakan smart-PLS 3.0. Hasil penelitian menunjukkan bahwa secara parsial hanya product knowledge yang berpengaruh signifikan terhadap minat penggunaan paylater (p-value = 0,000) dengan kontribusi dominan sebesar 64,5%. Sementara itu, digital marketing dan hedonisme tidak berpengaruh signifikan secara individual. Namun, secara simultan ketiga variabel mampu menjelaskan 82,7% variabilitas minat penggunaan (R² = 0,827). Temuan ini menunjukkan bahwa pertimbangan rasional berbasis pengetahuan produk lebih menentukan dibandingkan faktor promosi digital dan motivasi emosional. Kebaruan penelitian terletak pada pengujian model integratif ketiga variabel dalam konteks hotel berbintang, yang sebelumnya lebih banyak diteliti pada sektor e-commerce. Studi ini berkontribusi pada pengembangan literatur perilaku konsumen dan memberikan implikasi manajerial berupa pentingnya strategi edukatif dalam pemasaran digital layanan paylater.